Perlindungan Hukum Nasabah PT. X (Nama Pt Dirahasiakan) Ditinjau Dari Undang-Undang Perlindungan Konsumen - Wilda Afifia; Sumriyah Sumriyah (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Revocation of PT. X carried out by the Financial Services Authority, this is because PT. X was unable to meet the solvency ratio set by OJK. The high difference between liabilities and assets is an accumulation of losses due to the sale of products similar to a saving plan. PT. X sells fixed yield products that are not matched by the company's ability to obtain returns from managing its investments. these conditions were engineered by PT. X so that the financial statements are not in accordance with actual conditions. So that the OJK ordered a stop to the marketing of products similar to a saving plan, imposed a warning sanction and then a restrictive sanction so that the OJK revoked the business license of PT. X on December 05, 2022. So from this the author is interested in discussing dispute resolution related to the rights of customers of PT. X which has experienced losses in terms of the Consumer Protection Act.